CONSUMERS TRUST IN THE GLOBAL BRANDS: EMPIRICAL ANALYSIS IN THE CONTEXT OF CONSUMER PERSPECTIVE - Deari, Hasim; Balla, Eldian (European Scientific Journal, ESJ, 2013)
The aim of this paper is to analyze and explore factors that influence consumers trust in the global brands. Summarizing relevant scientific articles and academic literature on brand trust, it was found that there is a need to conduct research which will be dedicated to the consumer trust in the global brands. Until now there is lack of study in this field of trust in the context of global brands and this will be research based in the scientifically way which will shred light in the existing discipline but new way of treatment of case. To be much scientifically this study weâ€Ÿll use hypotheses in order to have relevant results from the consumersâ€Ÿ perspective. However, in this study survey methodology will take place, in terms that later to explore deeply significance influence of factors that have impact in the global brand trust. The results that weâ€Ÿll get will have one positive impact in the field of branding, respectively in the field of global brand trust. A total of 2010 questionnaire responses were used to empirically test the consumer trust for global brands. This study found that the brand trust has a significant influence in the customer loyalty. In addition, Brand trust has a positive impact on the consumer preference. As well as, the reliability scale for all variables that has been used in this study were .802 (Cronbach’s Alpha = .802)